STRUKTUR ORGANISASI DAN PROGRAM KERJA KOMITE SEKOLAH DI SDN 060912 KECAMATAN MEDAN DENAI - Vica Amalia; Hably Rizki Alfin Syukri Nasution; Tri Yolanda Putri; Esa Fakhriyah Lubis; Radianti (CV. Arsy Persada Quality, 2024)
A work program is an arrangement of work activity plans that have been designed and mutually agreed to be implemented within a certain period of time. The work program must be created in a directed manner, because it will become the organization's guide in achieving a goal. This research aims to find out what the organizational structure of the work program of SDN 060912 Medan Denai District is. The main role of the school committee can be divided into three, namely: 1. Advisory agency. The school committee provides considerations to the school principal in formulating and implementing educational policies in school. 2. Supporting agency (supporting agency) of the school committee plays a supporting role in the implementation of education in schools. 3. The school committee mediator becomes a communication bridge between the school, parents and the community. Improving the quality of school committees is an important step in advancing education in Indonesia. By improving the quality of school committees, it is hoped that school committees can contribute more optimally in improving the quality of education in schools.